Analysis of the Implementation of the Regional Financial Management Information System (SIPKD) in Regional Financial Management in the City of Padang Panjang - Ade Irawati; Aldri Frinaldi (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This study aims to analyze the implementation ofRegional Financial Management Information System (SIPKD)and analyze the factors that hinder the implementationRegional Financial Management Information System (SIPKD) in Regional Financial Management in Padang Panjang City. The type of research that will be used is qualitative research,with a descriptive approach. Data collection techniques were carried out through observation, interviews and recording. This study uses the analysis technique Manual Data Analysis Procedure (MDAP) to analyze the interview transcription data that has been obtained in the field. The findings of this study use George C. Edwards III's theory of policy implementation, which can be seen in the implementation of SIPKD for regional financial management that has not been optimal. This is due to not being optimal in socialization, employees who are still not proficient in the use of SIPKD, supporting facilities are not maximized, the network in the operation of SIPKD sometimes has errors and information has not been updated on the website, and the organizational structure is not in accordance with its field in Regional Financial Management in accordance with the recommendations. from the Ministry of Home Affairs